2022
DOI: 10.3390/ijms23169312
|View full text |Cite
|
Sign up to set email alerts
|

Sex as Biological Variable in Cardiac Mitochondrial Bioenergetic Responses to Acute Stress

Abstract: Cardiac dysfunction/damage following trauma, shock, sepsis, and ischemia impacts clinical outcomes. Acute inflammation and oxidative stress triggered by these injuries impair mitochondria, which are critical to maintaining cardiac function. Despite sex dimorphisms in consequences of these injuries, it is unclear whether mitochondrial bioenergetic responses to inflammation/oxidative stress are sex-dependent. We hypothesized that sex disparity in mitochondrial bioenergetics following TNFα or H2O2 exposure is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…Several studies have reported fundamental data regarding the cardiac response to sepsis and sex dimorphism [ 25 , 26 , 27 ]. Estrogen modulates several acute injury-related myocardial responses.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Several studies have reported fundamental data regarding the cardiac response to sepsis and sex dimorphism [ 25 , 26 , 27 ]. Estrogen modulates several acute injury-related myocardial responses.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Mitochondria are responsive to stress (705), and dysfunction is linked to CVD, MDD and chronic stress (706)(707)(708)(709)(710). Mitochondrial dysfunction may be a common link between chronic stress and multiple diseases (711).…”
Section: Other Pathophysiological Influences Of Chronic Stressmentioning
confidence: 99%
“…Experimental studies also demonstrate broad "mito-protective" functions of oestrogens (717-719), which directly enhance mitochondrial oxidative phosphorylation (720,721). Apparent resilience of female cardiac mitochondria to acute stressors has been linked to direct effects of oestrogen (705). Others link improved ischaemic tolerance in female mouse hearts to oestrogen dependent improvements in mitochondrial connexin-43 content and phosphorylation (722).…”
Section: Other Pathophysiological Influences Of Chronic Stressmentioning
confidence: 99%
“…Studies also suggest that mitochondria are protected from cardiac stress in the female heart. Female cardiomyocytes were shown to have improved mitochondrial respiration versus male cells in response to hydrogen peroxide and TNFα and preserved mitochondrial membrane potential in response to TNFα; interestingly, treatment of male cardiomyocytes with E2 recapitulated the protection shown in female cardiomyocytes [ 83 ]. Female mouse hearts also have higher mitochondrial mass compared with males, with male mitochondria having significantly rounder, more fragmented mitochondria; however, most of the functional analyses in this study were performed in brain mitochondria [ 84 ], so it is unclear whether these differences can be generalized to the cardiac mitochondrial pool.…”
Section: Sexual Dimorphism In Processes Known To Contribute To Post-i...mentioning
confidence: 99%